E-Health Literacy and Adherence to Health Protocols Among Self-Quarantined Patients with COVID-19 in a Sub-district in West Java - Hesty Utami Ramadaniati; Sondang Khairani; Nurul Azizah (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2023)
During the Coronavirus Disease-2019 (COVID-19) pandemic, valid information was crucial and electronic health literacy (EHL) plays a significant role in public adherence to health protocols. This study aimed to evaluate the pattern of COVID-19 information-seeking, and the association between EHL, COVID-19 knowledge, and health protocol adherence among patients with COVID-19 during self-quarantine. Data were collected through an online survey sent to self-quarantined COVID-19 patients during March – December 2020 in a sub-district in West Java. Spearman tests were used to evaluate the relationship between EHL with COVID-19 knowledge, and EHL with health protocol adherence. There were 56 respondents with more than half being female (58.9%), university graduates (64.3%) and having good health status level (57.1%). Social media were the commonest online sources. During self-isolation, the frequency of Internet use increased (i.e., every day) with information on vitamins and supplements as the most commonly searched. Respondents had high scores on EHL (mean= 20.0), knowledge (mean = 8.89/10, SD = 1.796), and adherence (mean = 26.98/30, SD = 3.066). This study found significant relationships between EHL and knowledge (p-value = 0.001, r = 0.436), and the adherence (p-value = 0.011, r = 0.339). In conclusion, EHL had a modest influence on COVID-19 knowledge and minor relationship with adherence to health protocols among self-quarantined patients with COVID-19.